Exploring nanotechnology solutions for improved outcomes in gastrointestinal stromal tumors - Sofia Gabellone; Silvia Vanni; Valentina Fausti; Giacomo Miserocchi; Chiara Liverani; Chiara Spadazzi; Claudia Cocchi; Chiara Calabrese; Davide Cavaliere; Carlo Alberto Pacilio; Giorgio Ercolani; Federica Pieri; et al. (Heliyon, 2024)
Objectives: Gastrointestinal stromal tumors, the most prevalent mesenchymal tumors (80 %) of the gastrointestinal tract, comprise less than 1 % of all gastrointestinal neoplasms and about 5 % of all sarcomas. Despite their rarity, Gastrointestinal stromal tumors present diverse clinical manifestations, anatomic locations, histological subtypes, and prognostic outcomes. Methods: This scoping review comprehensively explores the epidemiology, clinical characteristics, diagnostic and prognostic modalities, as well as new therapeutic options for Gastrointestinal stromal tumors. Results: A particular focus is placed on the promising role of bio-nanomaterials as multifunctional agents for drug delivery and 3D tumor microenvironment modeling. Bio-nanomaterials offer promising opportunities for targeted drug delivery, overcoming treatment resistance, and improving therapeutic efficacy. Conclusion: Despite significant advancements, Gastrointestinal stromal tumors remain a complex clinical entity with ongoing challenges. The integration of nanotechnology into Gastrointestinal stromal tumors management offers the potential to enhance patient outcomes. Future studies should prioritize the development and evaluation of nanomaterial-based therapies in clinical trials to facilitate the translation of laboratory discoveries into real-world clinical applications.